Financial development and economic growth in Ethiopia: Is there a causal link? - Seyoum Teffera Mengesha; Eva Berde (Cogent Economics & Finance, 2023)
The relationship between financial development and economic growth has been widely debated in the economics literature, but the results have been inconsistent and vary between the short and long run. In this study, we investigate the causal relationship between financial development and economic growth in Ethiopia using annual data from 1980 to 2021. We employ the Toda-Yamamoto causality test and the nonlinear autoregressive distributed lag (NARDL) modeling framework to analyze the data. Our results show that none of the variables are stationary at the level, but after applying first differences, all variables become stationary. Using the Toda-Yamamoto causality test, we find no causality running from financial development to economic growth, but there is evidence of reverse causality from economic growth to financial development. Furthermore, the NARDL model results suggest that economic growth drives financial development, and the relationship between financial development and economic growth in Ethiopia is nonlinear and asymmetric. Specifically, neither positive nor negative shocks to economic growth affect financial development in the short run, but both affect it in the long run and in joint short run and long run effects. We conclude from our study that financial development may not guarantee economic growth without building better institutions and following sound and stable fiscal policies. Consequently, constructing an effective economic growth strategy that maintains financial development is crucial. Our findings have significant implications for policymakers, academics, and investors and underscore the importance of informed decision-making based on a thorough understanding of the relationship between financial development and economic growth.
Keywords: 330; ARDL model; causality; cointegration; developing country; economic growth; financial development; Toda-Yamamoto Test